Elementary Teachers’ Academic Preparation and Performance - Eustaquio, Ryan P.; Espiritu, Raymond D. (Future Science / FSH-PH Publications, 2025)
The objective is to study was the Elementary Teachers’Academic Preparation and Performance in order to determine the backdrop information for an intervention, multidimensional collaborative with all stakeholders of education community in Castillejos District. This utilized a descriptive-survey research design with the instrument developed in PPST being modified and adopted for data collection. Two hundred forty-eight individuals were included in this study. Findings of the study reveal that Teachers Competence is at a high level in Lee and Lean skills, learning environment, learner diversity assessment and reporting, community linkages & curriculum planning Community linkages & professional Engagements Personal Growth and Profession Development. The variation in teaching effectiveness based on professional status and monthly salary is statistically significant with respect to knowledge of content, pedagogy, diversity of learners; curriculum organization and planning; evaluation and reporting as well as personal growth /professional development. No statistically significant difference is noted in Teaching Performance based on Learning Environment when respondents are grouped according to gender, age, civil status, teaching position/rank and monthly salary. It is therefore suggested, in this study that:, teachers should participate in work shop and seminars, upgrading for higher degrees and certificate holders, digital literacy training for teachers and curriculum development. Involve the community in the school room, field trips and activity Theories to help create a learning environment and parent classes on How to help their child learn at home or He parents needs to understand the curriculum. Additional research can be performed to confirm the findings of the current study.